2022
DOI: 10.7759/cureus.31997
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Nerve Impairment Associated With COVID-19 Infections: A Systematic Review

Abstract: The COVID-19 pandemic has created huge economic and healthcare burdens. In most cases, the virus affects the lungs and causes respiratory symptoms. Additionally, its impact on the cranial nerves remains unclear. We thus aimed to investigate cranial nerve dysfunction in patients with COVID-19 infection.We conducted a systematic literature search of relevant and eligible literature in five databases: PubMed, Web of Science, Medline, EBSCO, and Google Scholar.Our sample included 21 case reports, one case series w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The facial nerve (cranial nerve VII), the glossopharyngeal nerve (cranial nerve IX), and the vagus nerve (cranial nerve X) innervate the anterior two-thirds of the tongue, the posterior one-third of the tongue, and the epiglottis region, respectively, to transmit information on tastants. Among them, the facial nerve is most commonly affected by COVID-19, followed by the glossopharyngeal nerve and the vagus nerve [ 64 ]. A possible link has been indicated between COVID-19 and facial nerve paralysis [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The facial nerve (cranial nerve VII), the glossopharyngeal nerve (cranial nerve IX), and the vagus nerve (cranial nerve X) innervate the anterior two-thirds of the tongue, the posterior one-third of the tongue, and the epiglottis region, respectively, to transmit information on tastants. Among them, the facial nerve is most commonly affected by COVID-19, followed by the glossopharyngeal nerve and the vagus nerve [ 64 ]. A possible link has been indicated between COVID-19 and facial nerve paralysis [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported cases of cranial nerve infections following COVID-19, as well as cognitive impairment due to diffuse white matter damage [23,24]. Symptoms such as loss of smell and Bell's palsy also result from olfactory and facial nerve involvement [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…One patient presented with peripheral nerve palsy that remitted soon after antiviral and glucocorticoid treatment, during hospitalization, and two patients presented with polyneuritis cranialis, one of them died during hospitalization because of COVID-19 complications and the other one was discharged with sequelae. In a systematic review, the most commonly affected nerves were the facial and abducens nerves ( 41 ). The mechanism of PNS involvement continues to be a subject of debate as there are theories in favor of direct viral invasion, but inflammation also plays an important role ( 5 , 42 ).…”
Section: Discussionmentioning
confidence: 99%